Rancang Bangun Aplikasi Marketplace Edukasi “Pasar Ilmu” - Oei Joviano Matthew Wijaya; Vic Jeremy Prajogo; Gafgarion Sudrajat Budi Darminto; Gracia Stefani Suharyadi; Siska Narulita; Sekarlangit Sekarlangit (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
The welfare of teachers in Indonesia, especially honorary teachers, is still very poor when compared to other ASEAN countries. There is a gap between the salaries of teachers in Indonesia and the salaries of teachers in several ASEAN countries. There have been several demonstrations carried out by teachers, especially honorary teachers, because the salary received is not in accordance with the performance that has been carried out. On the other hand, there is a problem of high unemployment in Indonesia. The factors causing the high unemployment rate in Indonesia are the mismatch of qualifications and the low quality of education in Indonesia, as well as limited job vacancies and the high need for employment. To overcome these problems, a new innovation is needed that can help the community in creating jobs and improving the quality of education in Indonesia. The Pasar Ilmu educational marketplace application was developed to overcome these problems. The development of this Pasar Ilmu application uses the prototype system development method. This research aims to create a system or application of the Pasar Ilmu educational marketplace that can help improve the quality of education in Indonesia as an application that can help honorary teachers to get additional income, help reduce unemployment in Indonesia, and provide flexible courses or lessons for students.